1998
DOI: 10.3109/00207459809003341
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Immunological and Inflammatory Processes in the Pathogenesis and THERAPY of Alzheimer's Disease

Abstract: The contribution of autoimmune processes or inflammatory components in the etiology and pathogenesis of Alzheimer's disease (AD) has been suspected for many years. The presence of antigen-presenting, HLA-DR-positive and other immunoregulatory cells, components of complement, inflammatory cytokines and acute phase reactants have been established in tissue of AD neuropathology. Although these data do not confirm the immune response as a primary cause of AD, they indicate involvement of immune processes at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 224 publications
0
14
0
Order By: Relevance
“…The concept that inflammation is associated with and contributes to the pathogenesis of neurodegenerative diseases, including Alzheimer's disease, is gaining considerable acceptance (McGeer et al, 1989;Frohman et al, 1991;Aisen, 1996;Veerhuis et al, 1996;Eikelenboom et al, 1998;McGeer and McGeer, 1998;Akiyama et al, 2000;Mrak and Griffin, 2001;Weggen et al, 2001). What remains equivocal is the elucidation of the underlying mechanisms and the identity of the mediators involved in initiating or regulating these processes (Goldbager et al, 1989;Breitner, 1996;Beard et al, 1998;Pasinetti, 1998;Pitchumoni and Doraiswamy, 1998;Popovic et al, 1998;Schubert et al, 1998;Yermakova et al, 1999;Cole and Ard, 2000). Recently, we localized CAP37 to the cerebral microvasculature of patients with Alzheimer's disease (Pereira et al, 1996b).…”
Section: Discussionmentioning
confidence: 99%
“…The concept that inflammation is associated with and contributes to the pathogenesis of neurodegenerative diseases, including Alzheimer's disease, is gaining considerable acceptance (McGeer et al, 1989;Frohman et al, 1991;Aisen, 1996;Veerhuis et al, 1996;Eikelenboom et al, 1998;McGeer and McGeer, 1998;Akiyama et al, 2000;Mrak and Griffin, 2001;Weggen et al, 2001). What remains equivocal is the elucidation of the underlying mechanisms and the identity of the mediators involved in initiating or regulating these processes (Goldbager et al, 1989;Breitner, 1996;Beard et al, 1998;Pasinetti, 1998;Pitchumoni and Doraiswamy, 1998;Popovic et al, 1998;Schubert et al, 1998;Yermakova et al, 1999;Cole and Ard, 2000). Recently, we localized CAP37 to the cerebral microvasculature of patients with Alzheimer's disease (Pereira et al, 1996b).…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, we found that in analogy to the therapeutic effect of amyloid-␤ immunization in a mouse model of Alzheimer's disease (3), immunization with prion protein peptide reduced the PrP Sc content of a transplanted neuroblastoma (38). Moreover, recent publications have described inflammatory cells and molecules in several neurodegenerative diseases, including Parkinson's (39), Alzheimer's (40,41), and experimental prion disease (42). These findings raise the possibility that Ag-specific T or B cells might influence the natural history of these neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The ␤-amyloid is a potent and direct neurotoxic agent, and it induces a cascade of cellular mechanisms, including activation of astrocytes and microglia. It is well known that reactive glial cells produce excessive excitatory amino acids such as glutamate and inflammatory cytokines, including interleukin 1, tumor necrosis factor-␣, and transforming growth factor-␤ (Popovic et al, 1998), that are proposed to play an important role in neuronal death. Moreover, recent studies have demonstrated that reactive glial cells also produce a number of chemokines (Yates et al, 2000;Giri et al, 2003).…”
mentioning
confidence: 99%